Silicon Materials - Zaidi, Beddiaf; Belghit, Slimen (IntechOpen, 2019)
Apart from oxygen, silicon is the most commonly occurring element on Earth. Silicon materials have many applications in the manufacturing technology of microelectronic components, integrated circuits, and photovoltaic generators. Circuit complexity and higher degrees of integration of components require constant improvement and control of silicon's properties. This book provides information on silicon materials, their use, and their impact on the modern world economy.